2019
DOI: 10.5194/jsss-8-285-2019
|View full text |Cite
|
Sign up to set email alerts
|

Close-to-process strain measurement in ultrasonic vibration-assisted turning

Abstract: Abstract. The application of ultrasonic vibration assistance in machining offers many benefits over conventional machining. In some machining processes, like the generation of geometrically defined microstructures by cutting, the interaction of the system components and the machining process can be particularly crucial with respect to the production result. Monitoring of ultrasonic vibration-assisted machining in terms of the in-process measurement of frequency and amplitude is currently realized by measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous work conducted by the authors investigated using strain gauges for monitoring an ultrasonic-assisted turning process. The results showed that using strain gauges enables the detection of the current vibration shape of the system and allows for in-process measurement of ultrasonic systems, which may be used in control systems in the future [17]. The ultrasonic system used by Kimme et al also included an additional piezoelectric disc in the transducer to monitor the vibration and control the excitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work conducted by the authors investigated using strain gauges for monitoring an ultrasonic-assisted turning process. The results showed that using strain gauges enables the detection of the current vibration shape of the system and allows for in-process measurement of ultrasonic systems, which may be used in control systems in the future [17]. The ultrasonic system used by Kimme et al also included an additional piezoelectric disc in the transducer to monitor the vibration and control the excitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Khambay et al [20,21] measured the cutting force during ultrasonic chisel cutting of bovine bone using a strain gauge and studied the relationship between the cutting force and the tool rake angle and cutting speed. Kimme et al [22] proposed a strain gauge based on the position close to the cutting edge to measure the induced strain of an ultrasonic horn, and pointed out that multiple measurement positions on the ultrasonic horn can also estimate cutting force and current modal shape. This provides a new approach and direction for ultrasonic cutting force measurement, while also raising requirements for measurement accuracy and reliability.…”
Section: Introductionmentioning
confidence: 99%